Effect of ethnocentrism and patriotism on the buying intention of Malaysian national car - Che Aniza Che Wel; Syed Shah Alam; Nor Rahimy Khalid; Suraya Akmar Mokhtaruddin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia is one of the Asian countries that triumph in producing national car with an outstanding achievements in automotive industry. Nowadays, Proton and Perodua are the famous Malaysian car brands among its citizens, where Perodua become the top of the list. Malaysian citizens appreciate and support Malaysian brand to demonstrate their ethnocentrism and patriotism. Therefore, it is inspiring to comprehend consumer buying intention, towards Malaysian national car. Thus, this study is intended to examine consumer’s buying intention of Malaysian national car by examining their ethnocentrism and patriotism by utilizing the Theory of Planned Behavior. This study was conducted in Klang Valley covering respondents from various occupational levels. The finding of this study indicates that, patriotism, attitude and subjective norm affect consumer buying intention toward Malaysian national car. Therefore, this finding provides evidence to the Malaysian car provider upon the degree of ethnocentrism and patriotism in influencing Malaysian consumer’s buying intention.